1998
DOI: 10.1289/ehp.106-1533492
|View full text |Cite
|
Sign up to set email alerts
|

Hexachlorobenzene as a possible major contributor to the dioxin activity of human milk.

Abstract: A dioxinlike compound is a compound that binds to the aryl hydrocarbon (Ah) receptor, results in dioxinlike effects, and bioaccumulates. These are the three factors for including dioxinlike chemicals in the toxic equivalency factor (TEF) concept. Risk assessment of dioxinlike compounds is based on using these TEFs. Hexachlorobenzene (HCB) has all three features and should therefore be included in this TEF concept. Relative potency values express the potency of a specific compound in comparison to 2,3,7, 8-tetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(36 citation statements)
references
References 70 publications
3
33
0
Order By: Relevance
“…Nevertheless, HCB was found at much higher levels (1-2 magnitudes higher) in sediments than the other contaminants. The sublethal effects observed in this field study were quite similar with those reported under HCB exposure (Van Birgelen, 1998). Therefore, it is possible that HCB may be considered as a possible major contributor to the endocrine effects on juvenile silver carp development in Ya-Er Lake, China.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Nevertheless, HCB was found at much higher levels (1-2 magnitudes higher) in sediments than the other contaminants. The sublethal effects observed in this field study were quite similar with those reported under HCB exposure (Van Birgelen, 1998). Therefore, it is possible that HCB may be considered as a possible major contributor to the endocrine effects on juvenile silver carp development in Ya-Er Lake, China.…”
Section: Discussionsupporting
confidence: 84%
“…On the one hand, thyroid hormones are iodinated biphenyl ethers and have close chemical structure similar to PCDD/F, PCBs, HCB and their metabolites. For instance, the PCB metabolite, 4 0 -hydroxy-3, 3 0 , 4, 5 0 -tetrachlorobiphenyl, and the HCB metabolite, pentachlorophenol may compete strongly with thyroxine for the binding sites on the carrier binding protein (Brouwer, 1990;van Birgelen, 1998). However, the exposure to HCB and PCBs may also increase the metabolism of thyroxin by glucuronidation.…”
Section: Discussionmentioning
confidence: 99%
“…1. WHO-TEF values published by van den Berg et al [19] were used to calculate the PCDD, PCDF, and dl-PCB TEQs, and the PCN and HxCBz TEQs were calculated using the TEFs reported by Noma et al [20] and van Birgelen et al [21], respectively. The average concentrations found were 54.7 pg g −1 (1.50 pg TEQ g −1 ) for the PCDDs, 99.6 pg g −1 (2.26 pg TEQ g −1 ) for the PCDFs, 266.3 pg g −1 (0.26 pg TEQ g −1 ) for the dl-PCBs, 256 pg g −1 (0.14 pg TEQ g −1 ) for the PCNs, 290 pg g −1 (0.03 pg TEQ g −1 ) for HxCBz, and 146 pg g −1 for PeCBz.…”
Section: Concentrations Of Up-pops In Fly Ash Samplesmentioning
confidence: 99%
“…The WHO-TEF 2005 values reported by Van den Berg et al [18] were used to calculate the TEQs for the PCDD/Fs and dlPCBs. The TEQs for the dioxin like PCNs (dl-PCNs) and HxCBz were calculated based on the relative potency factors (RPFs) reported by Noma et al [19] and van Birgelen [20], respectively. Table 2 shows that the average WHO-TEQ values of PCDD/Fs measured in the flue gas samples at P1 and P2 in this study were 47.1 and 11.…”
Section: Concentrations Of Unintentional Pops Emitted From Thermal Wimentioning
confidence: 99%